MAPPING THE LITHOSPHERE-ASTHENOSPHERE BOUNDARY THROUGH CHANGES IN SURFACE-WAVE ANISOTROPY - Plomerova J.; Kouba D.; Babuska V. (My University, 2002)
The alignment of olivine crystals is considered as the dominant source of seismic anisotropy in the subcrustal lithosphere and asthenosphere. Different components of large-scale anisotropy can be traced in depth distributions of the radial and azimuthal anisotropy of surface waves. We propose a global model of the lithosphere-asthenosphere boundary (LAB) as a transition between a 'frozen-in' anisotropy in the lithosphere to anisotropy in the sublithospheric mantle related to the present-day flow. Due to different orientations of velocity maxima in the anisotropic subcrustal lithosphere and the asthenosphere, the velocity contrast related to the LAB can increase in particular directions. Because of their long wavelengths and horizontal propagation, surface waves suffer from poor lateral resolution. However, surface waves with various wavelengths allow us to map gross features of the LAB with a good vertical resolution. We estimate depths to the LAB to be between 200 and 250 km for the Precambrian shields and platforms, around 100 km for the Phanerozoic continental regions and 40-70 km beneath oceans from the world-wide depth distribution of the radial and azimuthal anisotropy of surface waves.
Keywords: LITHOSPHERE-ASTHENOSPHERE BOUNDARY; SURFACE WAVES; POLARISATION (RADIAL); AZIMUTHAL ANISOTROPY; Cambrian; Precambrian; Paleozoic::Cambrian; Precambrian; Палеозой::Кембрийская; Докембрий